Flexural strengthening of reinforced concrete beams using fabric reinforced Alkali-Activated Slag matrix - Shen, Xinyu; Chen, Weiwei; Li, Bo; Hancock, Craig Matthew; Xu, Yidong (Elsevier Ltd, 2020)
Old Reinforced Concrete (RC) buildings are facing different degrees of structural deterioration and require proper strengthening to enhance their structural performance as well as to extend their life span. Fabric reinforced Alkali-Activated Slag (AAS) matrix is proposed to strengthen RC beams in this study. Seven RC beams with and without strengthening were prepared and tested under four-point bending. Test results indicate that use of AAS matrix as replacement for conventional cement-based matrix can change the failure mode of the strengthened beams from end-debonding of strengthening layer to slippage combined with rupture of fabric. The AAS-based strengthening strategy is able to enhance the loading capacity and flexural stiffness of RC beams as well as to reduce the strain of tensile reinforcements. Except the specimens failed in the premature debonding, increasing the fabric amount in the strengthening scheme improves the loading capacity of beams. In an optimal case, the yielding and ultimate loads of the strengthened beams are enhanced by 22.2% and 26.4%, respectively. Moreover, an analytical model was developed to predict the characteristic loads of the fabric reinforced AAS matrix strengthened beams. It shows that the analytical model could overestimate the yielding and ultimate loads of the strengthened beams, probably due to slippage and reduced synergistic effect of fabric bundles in the strengthening system. Based on that, two efficiency factors of 0.35 and 0.25, taking account of the area of effective fabric, are obtained and recommended to estimate the yielding and ultimate loads of fabric reinforced AAS matrix-strengthened beams, respectively.